2022
DOI: 10.2147/ccid.s324331
|View full text |Cite
|
Sign up to set email alerts
|

Patient Quality of Life Improvement in Bullous Disease: A Review of Primary Literature and Considerations for the Clinician

Abstract: Autoimmune and inherited bullous disorders are rare skin diseases that may have a profound negative impact on quality of life (QOL). Common symptoms include pain, pruritus, and scarring, and complications may result in the loss of the ability to perform daily tasks. Diagnosis may have a negative psychological impact, and ongoing management may require a significant allocation of time and resources by both patients and providers. To provide patient-centered care, consideration of these factors is of utmost impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 74 publications
(128 reference statements)
0
1
0
Order By: Relevance
“…e equal gender distribution among study participants as noted by us was consistent with the literature on pemphigus vulgaris and bullous pemphigoid; however, a female predominance was noted by El Hafeez et al [3,9] Our observation of a higher proportion of patients manifesting bullous pemphigoid than pemphigus vulgaris was discordant with the findings of Sobhan et al [10] e previous authors have drawn attention to the adverse impact of pemphigus vulgaris and bullous pemphigoid on the quality of life of the affected. [11] Specific tools to assess the quality of life in autoimmune bullous diseases are introduced (autoimmune bullous disease quality of life and treatment of autoimmune bullous disease quality of life), since it was suggested that the DLQI questionnaire is not disease-specific. [12,13] However, Ferries et al, after their prospective analysis of the correlation between disease severity scores in different autoimmune bullous diseases and quality of life assessed by different tools, did not find any added benefit for autoimmune bullous disease-specific tools over DLQI.…”
mentioning
confidence: 99%
“…e equal gender distribution among study participants as noted by us was consistent with the literature on pemphigus vulgaris and bullous pemphigoid; however, a female predominance was noted by El Hafeez et al [3,9] Our observation of a higher proportion of patients manifesting bullous pemphigoid than pemphigus vulgaris was discordant with the findings of Sobhan et al [10] e previous authors have drawn attention to the adverse impact of pemphigus vulgaris and bullous pemphigoid on the quality of life of the affected. [11] Specific tools to assess the quality of life in autoimmune bullous diseases are introduced (autoimmune bullous disease quality of life and treatment of autoimmune bullous disease quality of life), since it was suggested that the DLQI questionnaire is not disease-specific. [12,13] However, Ferries et al, after their prospective analysis of the correlation between disease severity scores in different autoimmune bullous diseases and quality of life assessed by different tools, did not find any added benefit for autoimmune bullous disease-specific tools over DLQI.…”
mentioning
confidence: 99%